Notification - registry of pesticide-sensitive persons - Buffington, E. J., author; McDonald, S. K., author; Colorado Environmental Pesticide Education Program, publisher (Colorado State University. Libraries, 2006)
Pesticide Applicators Act, State of Colorado Title 35 Article 10. This fact sheet describes what the Registry of Pesticide- Sensitive Persons is, how to be placed on the registry, and how applicators must notify the public of pesticide applications.
Notification requirements - registry of pesticide-sensitive persons
CEPEP 10/01, updated 6/06.
PLEASE NOTE: This fact sheet is a historical document and some information may not reflect current federal and state laws and regulations and best practices.
Keywords: Pesticides -- Application -- Colorado; Pesticides -- Risk mitigation -- Colorado; Human beings -- Effect of pesticides on